Ecocriticism Concepts in Robert Frost’s “Out, Out-“ and “Stopping by Woods on a Snowy Evening” - Yustisiana, Rr. Arielia; Sari, Christina Maya Iriana (Universitas Negeri Semarang, 2024)
The research aims to discuss the concepts of ecocriticism in Robert Frost’s poems. There are two poems that will be discussed, namely “Out, Out-“ and Stopping by Woods on a Snowy Evening.” The two poems are chosen as the primary data of the research because both poems depicts human and nature interaction. Ecocriticism itself is a literary theory that examines the relationship between literature and the natural world. It focuses on the setting of the two poems and human and nature relation. Descriptive research is chosen as the method of research because this research aims accurately describes a phenomenon of human and natural world in Robert Forst’s poems. In terms of literary study, there are three literary approaches that are relevant in the research. Structural and formalist approaches are the general ones when the research takes data from a poem, while the specific literary approach is ecocriticism approach. “Out, Out-“ and “Stopping by Woods on a Snowy Evening” are two of Robert Frost’s poem that portray the relation between human and natural world. They can be analyzed through ecocritical lens to explore the complex interplay between humans and nature, ecological consequences of human actions, and the intersection of human existence and the natural world.